Food Safety and Environmental Awareness of Street Food Vendors of the Dhaka University Campus, Bangladesh (Bangladesh Journal of Zoology, 2020)
Many street vendors earn their livelihoods by selling foods and drinks at the campus of University of Dhaka. Their continuous presence and activities make them one of the key stakeholders of the campus. Both the vendors and customers dispose garbage indiscriminately in the vicinity, which makes the campus dirty, unclean and unhygienic. The aim of this study was to evaluate the environmental awareness and food safety practices among the food vendors with a view to recommend measures to uplift the campus environment. A mixed method was adopted for the study, in which 44 street vendors and 54 consumers were selected purposively from the campus. The results show that the vendors are not aware of food safety issues. The study recommends several measures, such as, designating vending places, registering all street food vendors, improving monitoring system and implementing non-formal environmental education programs for the vendors on food safety and environmental awareness.Bangladesh J. Zool. 48(1): 181-188, 2020